When thyroid labs do not add up, physicians should ask patients about biotin supplements. Issue 3 (31st March 2020) - Lundin, Michael S; Alratroot, Ahmad; Abu Rous, Fawzi; Aldasouqi, Saleh
Abstract : A 69-year-old woman with a remote history of Graves' disease treated with radioactive iodine ablation, who was maintained on a stable dose of levothyroxine for 15 years, presented with abnormal and fluctuating thyroid function tests which were confusing. After extensive evaluation, no diagnosis could be made, and it became difficult to optimise the levothyroxine dose, until we became aware of the recently recognised biotin-induced lab interference. It was then noticed that her medication list included biotin 10 mg two times per day. After holding the biotin and repeating the thyroid function tests, the labs made more sense, and the patient was easily made euthyroid with appropriate dose adjustment. We also investigated our own laboratory, and identified the thyroid labs that are performed with biotin-containing assays and developed strategies to increase the awareness about this lab artefact in our clinics.